Ganymede [videorecording (DVD)] - Holt, Coby; Doww, Jordan; Castelblanco, Pablo; Koechner, David, 1962- (Vantage Media, 2026)
When a smalltown wrestling star develops a crush on an openly gay classmate, he begins to be stalked by a grotesque creature that invades his thoughts, all the while struggling to live up to the standard set by his legacy-obsessed Dad.